New insights into the phylogenetic position of Hymenidium dentatum (Apioideae, Apiaceae) inferred from nrDNA and morphological evidence - Guo, Xian-Lin; Gou, Wei; Peng, Chang; Zhou, Song-Dong; He, Xing-Jin (Phytotaxa, 2020)
Hymenidium dentatum (Wall. ex DC.) Pimenov & Kljuykov was a little-known species that was regarded as endemic to the Himalayan region. It is known that many species are under-collected impeded taxonomic studies and the traditionally recognized genera Pleurospermum (Hymenidium and Pterocyclus) were polyphyletic group. In this study, two naturally occurring populations of H. dentatum were discovered in China and morphological traits and ITS sequence data were studied to confirm the phylogenetic position of H. dentatum, which was located in Sinodielsia clade and close to the generic type of Hymendium. A comprehensive description of H. dentatum along with distribution, habitats and specimens examined and discuss suggestions for the conservation of this species were carried out comprehensively referring to our fieldwork.